Combatting sepsis-induced myocardial dysfunction: emerging mechanisms and immunomodulatory breakthroughs - Liu, Can; Liu, Hanfeng; Li, Yunxing; Zeng, Yangxi; Wang, Xinyu; Mou, Yuhan; Liao, Bin; Wan, Juyi (Frontiers in Immunology, 2025)
Sepsis-induced myocardial dysfunction (SIMD) critically contributes to mortality in systemic inflammatory responses, driven by multifaceted mechanisms including dysregulated inflammation, immunosuppression, oxidative stress, and autonomic dysfunction. Emerging pathways involve m6A RNA methylation (mediated by methyltransferase METTL3), which coordinates inflammation, apoptosis, and ferroptosis through transcriptomic rewiring. Extracellular vesicles (EVs) serve dual roles: propagating injury via microRNA-885-5p/HMBOX1-induced pyroptosis and delivering therapeutic cargo (e.g., microRNA-223) to suppress inflammation. Mitochondrial dysfunction, marked by reactive oxygen species (ROS)-NOD-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome activation and impaired sarco/endoplasmic reticulum calcium ATPase 2a (SERCA2a) stability, exacerbates metabolic disorder. Autonomic neuromodulation strategies, such as electroacupuncture and noninvasive vagus nerve stimulation, attenuate cardiac injury by rebalancing neuroimmune interactions. Complement hyperactivation (C5a-C5a receptor axis) and immune checkpoint inhibitors (e.g., anti-programmed death-ligand 1 [PD-L1] antibodies) show preclinical efficacy. However, challenges persist in addressing immune heterogeneity, dynamic biomarker profiling, and optimal therapeutic timing. This review bridges mechanistic discoveries to clinical innovation, proposing a paradigm shift toward precision therapies. Future research must bridge mechanistic insights with clinical innovation. By harmonizing pathophysiological understanding with precision medicine approaches, this synthesis underscores the potential to transform SIMD management from supportive care to targeted functional recovery.